Selective partitioning of plant proteins during emulsification impairs foam stability: conformational changes of aqueous-phase residues relative to animal proteins - Yiqiu Deng; Wanjun Han; Yiting Lin; Xiuhang Chai; Fengxiang Chen; Yuanfa Liu (Food Hydrocolloids, 2026)

Synergy between monomer oxygen vacancies and oxygen vacancy clusters in MnO2 enables efficient catalytic decomposition of N2O - Hui Dang; Wanjun Zhao; Chengming Zhang; Ruifang Wu; Liangliang Zhang; Ke Zheng; Shize Hu; Xiangqian Lin; Aiping Jia; Zhenxing Ren; Yongzhao Wang; Yongxiang Zhao (Journal of Hazardous Materials, 2026)

Key odorants driving aroma transformation during aging process in Liubao tea: A sensory and chemical perspective - Ying Yang; Ruijin Qiu; Qiushuang You; Wanjun Ma; Yuhui Zhang; Yan Zhao; Gaozhong Yang; Yue Zhang; Zhi Lin; Yin Zhu; Haipeng Lv (Food Chemistry, 2025)

Synergistic interaction between hydrophilic polyglycerol fatty acid esters and sucrose esters regulates fat crystallization at the water/oil interface in highly unsaturated whipped emulsions - Wanjun Han; Yiqiu Deng; Yiting Lin; Farah Zaaboul; Qiuling Huangfu; Yanwen Sun; Xiuhang Chai; Chin-Ping Tan; Yuanfa Liu (Chemical Engineering Journal, 2025)

Application of multi-dimensional isotope fractionation to characterize the biotic and abiotic transformation mechanisms of the herbicide 2,4-dichlorophenoxyacetic acid - Jukun Xiong; Yongyu Liang; Chang Yuan; Suyun Chen; Meicheng Wen; Wanjun Wang; Qinhao Lin; Yingxin Yu (Journal of Hazardous Materials, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

Diffusion coefficients of water in CO2 under the condition of CO2 sequestration in saline aquifers - Zhe Wang; Linlin Lin; Huirong Guo; Wanjun Lu (Journal of Hydrology, 2025)

Native polymer degradation capacity of microorganisms in agricultural soils - Zahra F. Islam; Pavel V. Cherepanov; Wanjun Xu; Helen L. Hayden; Elena Colombi; Zhixing Lin; Omid Mazaheri; Frank Caruso; Deli Chen; Hang-Wei Hu (Science of The Total Environment, 2025)

Pulmonary surfactant biogenesis blockage mediated polyhexamethylene guanidine disinfectant induced pulmonary fibrosis - Xin Li; Jianzhong Zhang; Mingyue Wang; Haonan Li; Wanjun Zhang; Jiayin Sun; Lin Zhang; Yuxin Zheng; Jing Liu; Jinglong Tang (Journal of Hazardous Materials, 2024)

Species discrimination of Fritillaria Bulbus using PCR-CRISPR/Cas12a-based nucleic acid detection - Dongfan Yang; Yanchao Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Wenzhe Ma (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Abnormal trial-to-trial variability in P300 time-varying directed eeg network of schizophrenia - Chanlin Yi; Fali Li; Jiuju Wang; Yuqin Li; Jiamin Zhang; Wanjun Chen; Lin Jiang; Dezhong Yao; Peng Xu; Baoming He; Wentian Dong (Medical & Biological Engineering & Computing, 2024)

Atmospheric VOCs in an industrial coking facility and the surrounding area: Characteristics, spatial distribution and source apportionment - Meicheng Wen; Weiqiang Deng; Jin Huang; Shu Zhang; Qinhao Lin; Chao Wang; Shengtao Ma; Wanjun Wang; Xin Zhang; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2024)

MsSPL12 is a positive regulator in alfalfa (Medicago sativa L.) salt tolerance - Shiwen Lin; Jie Yang; Yanrong Liu; Wanjun Zhang (Plant Cell Reports, 2024)

Corrigendum to “Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC-MS” [Food Chem. 414 (2023) 135739] - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

A rapid approach to evaluating ground surface conditions for shale gas extraction in mountainous areas - Xiaofeng Xu; Wanzhong Shi; Xinyu Zhang; Jianwei Lin; Wanjun Lu; Qian Feng; Xianglin Chen; Ren Wang; Xiaoming Zhang (Gas Science and Engineering, 2023)

Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC–MS - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Carbon emission evaluation of prefabricated concrete composite plates during the building materialization stage - Xiaojuan Li; Wanjun Xie; Ting Yang; Chengxin Lin; C.Y. Jim (Building and Environment, 2023)

Dissolution migration of gas, a mechanism to enrich ethane near the BSR and increase upwardly C1/C2 ratios in the hydrate-occurring zones: Insight from pore-scale experimental observation - Hui Li; Xuekang Lu; Lin Wang; Wenjing Wang; Tianhua Li; Wanjun Lu; Yong Chen (Frontiers in Marine Science, 2023)
Most experiments show that gas hydrates are often enriched in C 2+ gases relative to the feeding gas source because of fractionation during hydrate crystallization directly from free gases and dissolved gases. However, sediments below and near the base of the gas hydrate stability zone (BGHSZ) in many ocean drilling program (ODP)/International Ocean Discovery Program (IODP) sites are relatively enriched in C 2+ hydrocarbon gases, compared with the hydrate-occurring zone above. It is still unclear what kind of process causes the abrupt decreases in C 1 /C 2+ ratios with the depth in headspace gas in sediments around seismic bottom-simulating reflector (BSR) and increasing upward C 1 /C 2 ratios in the hydrate-occurring zone. To test the “dissolution/migration mechanism” and its links to the enrichment of ethane near the BSR and increasing upward C 1 /C 2 ratios in the hydrate-occurring zone, we performed a series of pore-scale experimental observations, simulating the gas dissolution–migration–hydration processes, and investigated the effects of the composition of feeding gases and temperatures on the composition of the hydrate grown under the dissolution–migration mechanism. Hydrates are grown from aqueous fluids supplied by the migration of gases dissolved from the capillary-trapped free gas in a capillary high-pressure optical cell, with different supplying gases (90 mol% CH 4 + 10 mol% C 2 H 6 , 80 mol% CH 4 + 20 mol% C 2 H 6 ) and a geothermal gradient (temperature from 278.15 to 293.15 K). The gas hydrate structure and composition were determined by quantitative Raman spectroscopy. Our study indicated that (1) under the dissolution–migration–hydration processes, the mole fraction of C 2 H 6 in hydrates is depleted compared with gas sources, which confirms that the dissolution–migration of gases is a mechanism to enrich ethane near the BSR; (2) the proportion of C 2 H 6 in structure I (sI) or structure II (sII) hydrates decreases with decreasing temperature, and decreasing temperature enlarges the difference of diffusion coefficient between methane and ethane and enhances the gas fractionation during migration, which could cause the increase upwardly C 1 /C 2 ratios in the hydrate-occurring zone. A simplified geological model was proposed to explain the variability of hydrate composition with depth in the hydrate-occurring zone and the fractionation of gases near the BSR.

Enhanced adsorption of benzo(a)pyrene in soil by porous biochar: Adsorption kinetics, thermodynamics, and mechanisms - Wanjun Wang; Jiaxin Lin; Shaobin Shao; Haojia Chen; Jiawei Dai; Yan Yang (Journal of Environmental Chemical Engineering, 2023)

Age-Related Reduction in Cortical Thickness in First-Episode Treatment-Naïve Patients with Schizophrenia - Yin Lin; Mingli Li; Yi Zhou; Wei Deng; Xiaohong Ma; Qiang Wang; Wanjun Guo; Yinfei Li; Lijun Jiang; Xun Hu; Nanyin Zhang; Tao Li (Neuroscience Bulletin, 2019)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)